2018
DOI: 10.1159/000495357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hybrid Therapy Comprising Peritoneal Dialysis and Hemodialysis on Acute Cardiovascular Events

Abstract: Background: The impact of hybrid therapy comprising peritoneal dialysis (PD) and hemodialysis on cardiovascular events in PD patients remains unclear. Objective: We aimed to evaluate the effect of hybrid therapy on cardiovascular events. Methods: A total of 93 PD patients undergoing hybrid therapy for ≥3 years were divided into 2 groups according to left ventricular ejection fraction (LVEF): lower ejection fraction (LEF [n = 29], LVEF < 60%) and normal ejection fraction (NEF [n = 64], LVEF ≥60%). Hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Fluid overload is common in PD patients [37][38][39][40][41][42][43][44] and an independent predictor of all-cause mortality [39,42]. Ng et al [41] reported that fluid overload was common in asymptomatic incident PD patients and a strong predictor of patient survival and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid overload is common in PD patients [37][38][39][40][41][42][43][44] and an independent predictor of all-cause mortality [39,42]. Ng et al [41] reported that fluid overload was common in asymptomatic incident PD patients and a strong predictor of patient survival and cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, some nephrologists start PD + HD therapy early after initiation of PD, believing that HD with little ultrafiltration in addition to PD preserves residual renal function and provides better nutritional status [ 13 ]. Many nephrologists utilize PD + HD therapy a few years following initiation [ 6 , 8 ] of PD when they judge that fluid and solute removal was insufficient with PD alone, though other nephrologists keep patients on PD alone until complete transition to HD. The decisions to start PD + HD therapy depend on the preferences of patients and their treating physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported about outcomes of PD + HD therapy. In previous studies, after initiation of combination therapy, authors observed reduction in human atrial natriuretic peptide levels [ 6 ], improvement in blood pressure control [ 7 ], reduction in left ventricular mass index [ 6–8 ], improvement in left ventricular ejection fraction [ 8 ], reduction in hospitalization for cardiac events [ 8 , 9 ] and improvement in quality of life [ 10 , 11 ]. These studies suggest that PD + HD therapy may improve cardiovascular (CV) outcomes by better fluid removal by adding once-weekly HD to PD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid therapies comprised of peritoneal dialysis (PD) and HD may also be a novel approach to better control volume and BP. One study reported an improvement in cardiac systolic function among 93 patients who underwent hybrid therapy for 3 years …”
Section: Current Strategies To Manage Volume Overloadmentioning
confidence: 99%
“…One study reported an improvement in cardiac systolic function among 93 patients who underwent hybrid therapy for 3 years. 42 Standard dialysis therapies can also be modified for better volume and BP control. Correct prescription of dry weight and achievement of this weight with each HD treatment may improve volume control and BP.…”
Section: Dialytic Strategiesmentioning
confidence: 99%